Focused Ion Beam Direct Fabrication of Subwavelength Nanostructures on Silicon for Multicolor Generation. Issue 8 (13th July 2018) - Garg, Vivek; Mote, Rakesh G.; Fu, Jing
Abstract: Color filtering via interaction of visible light with nanostructured surfaces offers high resolution printing of structural colors. A novel approach for color filtering in reflection mode via direct fabrication of subwavelength nanostructures on high‐index, low‐loss, and inexpensive silicon (Si) substrate is developed. Nanostructures having a unique geometry of tapered holes are fabricated exploiting the Gaussian nature of a gallium source focused ion beam (FIB). The fabrication process is rapid and single‐step, i.e., without any pre‐ or postprocessing or mask preparation in contrast to previously reported nanostructures for color filtering. These nanostructures are tunable via FIB parameters and a wide color palette is created. Finite‐difference time‐domain (FDTD) calculations reveal that the unique tapered nanohole geometry facilitates enhanced color purity via selective absorption of a narrow band of incident light wavelengths and makes it possible to obtain a wide variety of colors suitable for realistic color printing applications. The proposed approach is demonstrated for color printing applications via fabrication of butterflies and letters on Si. Abstract : Subwavelength nanostructures comprised of a periodic array of novel tapered nanoholes on silicon are directly fabricated using Focused Ion Beam (FIB) milling. The nanohole resonator arrays enable filtering of colors in a reflection mode and a wide color palette is demonstrated by varying the diameter " D " and the period " P " of the nanohole array.